PRIMER REGISTRO DE TORPEDO PERUANA CHIRICHIGNO (ELASMOBRANCHII: TORPEDINIDAE) PARA EL PACIFICO COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
Morphologic information about two individuals of Torpedo peruana from the Colombian Pacific coast is presented. The species had not been reported before from tropical South American waters; this finding ratifies its validity after its redescription.